Valor agregado de instituições de ensino superior em Minas Gerais para os cursos de Direito, Administração e Engenharia Civil - Soares,José Francisco (2001)
This article presents the results of a study employing the added value methodology to evaluate the effect of institutions of higher learning in Minas Gerais States on the performance of their students in the so-called Joint National Board Exams (Provão). The added value methodology allows to control substantive factors influencing academic performance and to capture the specific effect of a teaching institution on the students final performance. The purpose is to help clarify and improve the procedures for evaluating institutions of higher learning as an important instrument for policy-making in education.